Development of a novel nano-sized anti-VEGFA nanobody with enhanced physicochemical and pharmacokinetic properties. (3rd October 2018) - Khodabakhsh, Farnaz; Norouzian, Dariush; Vaziri, Behrouz; Ahangari Cohan, Reza; Sardari, Soroush; Mahboudi, Fereidoun; Behdani, Mahdi; Mansouri, Kamran; Mehdizadeh, Ardavan
Abstract: Since physiological and pathological processes occur at nano-environments, nanotechnology has considered as an efficient tool for designing of next generation specific biomolecules with enhanced pharmacodynamic and pharmacodynamic properties. In the current investigation, by control of the size and hydrodynamic volume at the nanoscale, for the first time, physicochemical and pharmacokinetic properties of an anti-VEGFA nanobody was remarkably improved by attachment of a Proline-Alanine-Serine (PAS) rich sequence. The results elucidated unexpected impressive effects of PAS sequence on physicochemical properties especially on size, hydrodynamics radius, and even solubility of nanobody. CD analysis revealed an increment in random coil structure of the PASylated protein in comparison to native one without any change in charge state or binding kinetic parameters of nanobody assessed by isoelectric focusing and surface plasmon resonance measurements, respectively. In vitro biological activities of nanobody were not affected by coupling of the PAS sequence. In contrast, the terminal half-life was significantly increased by a factor of 14 for the nanobody-PAS after single dose IV injection to the mice. Our study demonstrated that the control of size in the design of small therapeutic proteins has a promising effect on the stability and solubility, in addition to their physiochemical and pharmacokinetic properties. The designed new anti-VEGFA nanobody could promise a better therapeutic agent with a long administration intervals and lower dose, which in turn leads to a better patient compliance. Size adjustment of an anti-VEGF nanobody at the nanoscale by the attachment of a natural PAS polymer remarkably improves physicochemical properties, as well as a pharmacokinetic profile without any change in biological activity of the miniaturized antibody. Graphical Abstract: